Forget about forgetting: structural barriers and severe non-adherence to antiretroviral therapy. Issue 4 (3rd April 2017) - Kalichman, Seth C.; Kalichman, Moira O.; Cherry, Chauncey
ABSTRACT: HIV infection is now clinically manageable with antiretroviral therapy (ART). However, a significant number of people with HIV do not benefit from ART because of non-adherence. This study examined the use of adherence strategies and barriers to adherence among persons at substantial risk for developing resistant virus (less than 75% adherent). People living with HIV ( n  = 556) who were less than 95% adherent to ART completed computerized interviews, were screened for active drug use, provided medical records for HIV viral load, and completed unannounced pill counts to monitor ART adherence and an assessment of adherence barriers. Based on pill counts, participants were defined as severely non-adherent (≤75% medications taken) and moderately non-adherent (>75% and <95% adherent). Results showed a broad array of memory devices were used to no avail across non-adherence groups. Individuals who were severely non-adherent were significantly more likely to attribute missing medications due to substance use and structural barriers, including running out of medications, inability to get to pharmacy, and inability to afford medications. Results suggest that interventions focused on memory lapses will be insufficient and should rather concentrate on substance use treatment and providing case management to resolve structural barriers to adherence.